Influence of sitting and sleeping posture in the appearance of deformities of the skeletal-muscular system in children. - José Julio Requeiro Molina; Yusimí Isaguirre Martínez; Ana María Machado Consuegra; Grabiela M. Requeiro Molina; Juana María Morejón Fernández; Ortelio Rodríguez Medina (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
-